Separate roles of IL‐6 and oncostatin M in mouse macrophage polarization in vitro and in vivo. Issue 3 (26th December 2017) - Dubey, Anisha; Izakelian, Laura; Ayaub, Ehab A; Ho, Lilian; Stephenson, Kyle; Wong, Steven; Kwofie, Karen; Austin, Richard C; Botelho, Fernando; Ask, Kjetil; Richards, Carl D
Abstract: Arginase‐1 (Arg‐1)‐expressing M2‐like macrophages are associated with Th2‐skewed immune responses, allergic airway pathology, ectopic B16 melanoma cancer growth in murine models, and can be induced by Oncostatin M (OSM) transient overexpression in vivo . Here, we compare OSM to the gp130‐cytokine IL‐6 in mediating macrophage polarization, and find that IL‐6 overexpression alone (Ad vector, AdIL‐6) did not induce Arg‐1 protein in mouse lungs at day 7, nor ectopic melanoma tumor growth at day 14, in contrast to overexpression of OSM (AdOSM). AdOSM elevated levels of IL‐4, IL‐5 and IL‐13 in bronchoalveolar lavage fluid, whereas AdIL‐6 did not. Bone marrow‐derived macrophages respond with Arg‐1 enzymatic activity to M2 stimuli (IL‐4/IL‐13), which was further elevated in combination with IL‐6 stimulation; however, OSM or LIF had no detectable activity in vitro . Arg‐1 mRNA expression induced by AdOSM was attenuated in IL‐6‐/‐ and STAT6‐/‐ mice, suggesting requirements for both IL‐6 and IL‐4/IL‐13 signaling in vivo . Ectopic B16 tumor burden was also reduced in IL‐6‐/‐ mice. Thus, OSM induces Arg‐1+ macrophage accumulation indirectly through elevation of Th2 cytokines and IL‐6 in vivo, whereas IL‐6 acts directly on macrophages but requires a Th2 microenvironment, demonstrating distinct roles for OSM and IL‐6 in M2 macrophage polarization. Abstract : The gp130 cytokines Oncostatin M and IL‐6 were compared in ability to induce M2‐like (Arginase+) macrophages in vivo and in vitro . OSM acted indirectly in vivo requiring IL‐6 and STAT6 signaling to induce M2 macrophages, without direct action on macrophages. While IL‐6 could act directly on macrophages, it required a Th2 environment both in vitro and in vivo to further induce M2 Arg+ cells, indicating distinct roles of OSM and IL‐6 in M2 cell accumulation/activation. See also: News and Commentary byRuckerl & Seoane